Can Good Citizens Lead the Way in Providing Quality Service? A Field Quasi Experiment - Hui, Chun; Lam, Simon S. K.; Schaubroeck, John (Academy of Management Journal, 2001)
In a field quasi experiment, customers were most satisfied with the service quality of the branch of a multinational bank where good organizational citizens had been trained as service quality leaders, and branch employees exhibited the highest conformance to the quality scheme of the bank. In a branch where service quality leaders were randomly selected for training, customer satisfaction and conformance improved more than they did in a branch where no service quality leaders were trained.